2015
DOI: 10.1523/jneurosci.1589-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

An Obesity-Predisposing Variant of the FTO Gene Regulates D2R-Dependent Reward Learning

Abstract: Variations in the fat mass and obesity-associated (FTO) gene are linked to obesity. However, the underlying neurobiological mechanisms by which these genetic variants influence obesity, behavior, and brain are unknown. Given that Fto regulates D2/3R signaling in mice, we tested in humans whether variants in FTO would interact with a variant in the ANKK1 gene, which alters D2R signaling and is also associated with obesity. In a behavioral and fMRI study, we demonstrate that gene variants of FTO affect dopamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 60 publications
5
78
1
Order By: Relevance
“…Impaired brain insulin signalling could therefore contribute to increased body fat content and increased waist circumference, as well as to reduced peripheral insulin sensitivity in carriers of both risk alleles. In addition, our results in combination with the finding of an altered midbrain response in participants carrying both polymorphisms during a reward learning task [42] indicate that the interaction of FTO and ANNK1 affects metabolic and behavioural brain networks.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Impaired brain insulin signalling could therefore contribute to increased body fat content and increased waist circumference, as well as to reduced peripheral insulin sensitivity in carriers of both risk alleles. In addition, our results in combination with the finding of an altered midbrain response in participants carrying both polymorphisms during a reward learning task [42] indicate that the interaction of FTO and ANNK1 affects metabolic and behavioural brain networks.…”
Section: Discussionsupporting
confidence: 65%
“…Specifically, an attenuated response to food in the striatum of risk-allele carriers was a predictor of further weight gain [41]. A recent study in humans identified an interaction between FTO and ANNK1 polymorphisms that determines midbrain activity during reward learning [42].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting, however, that even within the cohorts of adults tested previously, there is little consistency in reported effects across studies. Moreover, with one exception (14), none of the prior work links FTO genotypic differences to neural differences in canonical reward regions despite the fact that previous studies have demonstrated a causal role of FTO in regulating dopaminergic transmission (12) and also in modulating mesocorticolimbic circuitry in adults (13). The effects reported here in children in ventral striatum function and structure, as well as the voxel-wise whole-brain exploratory analysis, constrain the FTO genotypic differences to canonical reward neurocircuitry.…”
Section: Discussionmentioning
confidence: 59%
“…Although the FTO gene is highly expressed in the brain (1), the mechanism by which this gene promotes unhealthy eating behaviors remains poorly understood. Previous studies have suggested that FTO alters dopaminergic midbrain circuitry (12,13). Thus, one possibility is that the FTO gene influences the early development and responsivity of reward-related brain structures, thereby predisposing individuals to develop patterns of unhealthy eating.…”
mentioning
confidence: 99%
“…First, variations in the fat mass and obesity-associated (FTO) gene are the strongest polygenic determinants of adiposity [32] and inactivation of this gene impairs DRD2-dependent neurotransmission and function in rodents [33] and DRD2-dependent learning in humans [34]. Second, the TaqIA RFLP, which is associated with variation in DRD2 receptor density [3538], was recently shown to interact with an FTO gene variant to influence adiposity, central and peripheral insulin resistance and DRD2-dependent learning [34, 39]. In both studies the influence of FTO on these phenotypes was found to be either greater in individuals who also possessed a copy of the TaqIA at-risk allele or dependent upon individuals also having this genotype.…”
Section: Why Drd2?mentioning
confidence: 99%